2013
DOI: 10.1002/aur.1275
|View full text |Cite
|
Sign up to set email alerts
|

Use of Birth Certificates to Examine Maternal Occupational Exposures and Autism Spectrum Disorders in Offspring

Abstract: The continuing rise in the prevalence of autism spectrum disorders has led to heightened interest in the role of nongenetic factors, including exogenous exposures, but little research has been conducted. To explore a possible role in autism etiology, we used data available from our prior studies to examine potential occupational exposures, as these may occur at higher levels than environmental exposures. Parental occupation was obtained from birth certificates for 284 children with autism and 659 controls, bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 33 publications
1
32
2
Order By: Relevance
“…33 A third retrospective case–control study of 284 children with ASD and 682 partially matched TD children of similar age from regions in the San Francisco Bay area reported that mothers of children with ASD were twice as likely (14.4 versus 7.2%) during gestation to work in an occupation with exposure to toxicants such as exhaust and combustion products (OR=12.0; 95% CI, 1.4–104.6) and disinfectants (OR=4.0; 95% CI, 1.4–12.0); paternal occupational exposure was not found to be associated with autism. 34 Finally, the fourth retrospective case–control study from Spain examined 70 children with ASD and 136 controls, and reported that parental occupational exposures to solvents (including paints, varnishes, lacquers, adhesives, glues, degreasing chemicals, cleaning supplies, dyes, polymers, plastics, textiles and printing inks) were associated with an increased risk of ASD when the mother (OR=2.88; 95% CI, 1.28–6.17) or the father (OR=2.81; 95% CI, 1.01–7.86) worked with solvents. 35 Collectively, these studies ranged from 70 to 1784 children and provided limited evidence for an association between exposures to other toxicants during gestation and ASD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 A third retrospective case–control study of 284 children with ASD and 682 partially matched TD children of similar age from regions in the San Francisco Bay area reported that mothers of children with ASD were twice as likely (14.4 versus 7.2%) during gestation to work in an occupation with exposure to toxicants such as exhaust and combustion products (OR=12.0; 95% CI, 1.4–104.6) and disinfectants (OR=4.0; 95% CI, 1.4–12.0); paternal occupational exposure was not found to be associated with autism. 34 Finally, the fourth retrospective case–control study from Spain examined 70 children with ASD and 136 controls, and reported that parental occupational exposures to solvents (including paints, varnishes, lacquers, adhesives, glues, degreasing chemicals, cleaning supplies, dyes, polymers, plastics, textiles and printing inks) were associated with an increased risk of ASD when the mother (OR=2.88; 95% CI, 1.28–6.17) or the father (OR=2.81; 95% CI, 1.01–7.86) worked with solvents. 35 Collectively, these studies ranged from 70 to 1784 children and provided limited evidence for an association between exposures to other toxicants during gestation and ASD.…”
Section: Resultsmentioning
confidence: 99%
“…17, 18, 19, 20, 21 Fourteen of the studies (39%) suggested evidence of a dose–effect relationship—that is, ASD risk was associated with higher estimated toxicant exposure levels as gauged by measuring biomarkers, 17, 18, 19, 20 a closer proximity to estimated toxicant exposures 25,27,30,38,39,47,48 or questionnaires. 24,33,34 One study reported that a genetic variant in MET was associated with a greater risk of ASD in children exposed to higher levels of air pollutants, suggesting that genetic factors may have a role in increasing susceptibility to toxicants in some ASD children.…”
Section: Resultsmentioning
confidence: 99%
“…Recent environmental factors associated with ASD have been identified through analysis of large data sets focusing on exposures or events during pregnancy or infancy. Although these associations are preliminary and cannot be considered causative, a partial list of environmental factors associated with an increase risk of ASD includes maternal exposure to environmental pollutants, 17,18 use of valproate during pregnancy, 19 maternal hypertension, diabetes, and obesity during pregnancy, 20 short interpregnancy interval, 21 and perinatal complications including low birth weight and prematurity, 22 as well as maternal immune 23 and endocrine 24 factors. Potential gene-environment interaction associated with ASD is an active area of research, and as results emerge, families will rely on PCCs for accurate information.…”
Section: What Is the Etiology Of Asd?mentioning
confidence: 98%
“…The seven studies of VOCs included in our review (Table 7) measured exposures with the following methods: (1) self-report or birth certificate report of parental exposure in the workplace and occupation, which was coded into multiple chemical classes based on the work duties and products manufactured 87,88 ; (2) parent report of exposure to “textiles” and “newly built homes” 89 ; and (3) a vehicle and factory emissions-based air pollutant model of the U.S. Environmental Protection Agency that models census tract levels of air toxics for selected years, the National-scale Air Toxics Assessment (NATA), including a study for which one of us (A.K.) was an author.…”
Section: Evidence Regarding Environmental Chemical Pollutantsmentioning
confidence: 99%
“…16,70,90 The NATA model predicted concentrations of over 30 air toxics in 1996 and over 180 air toxics in 1999, 2002, and 2005. In summary, these exposure methods had the following strengths: (1) corresponding to the pertinent prenatal and early postnatal time periods; (2) independent expert verification/coding of occupational exposures 87,88 ; and (3) prospective measurement, along with a reduced chance of a recall bias, in the studies of air toxics and the occupation study based on birth certificate-reported occupation. 16,70,88,90 …”
Section: Evidence Regarding Environmental Chemical Pollutantsmentioning
confidence: 99%